Frontispiz: Structurally Defined Water‐Soluble Metallofullerene Derivatives towards Biomedical Applications. (9th January 2023) - Li, Yanbang; Biswas, Rohin; Kopcha, William P.; Dubroca, Thierry; Abella, Laura; Sun, Yue; Crichton, Ryan A.; Rathnam, Christopher; Yang, Letao; Yeh, Yao‐Wen; Kundu, Krishnendu; Rodríguez‐Fortea, Antonio; et al.
Abstract : Fullerenes . In their Research Article (e202211704 ), Jianyuan Zhang et al. report the synthesis of metallobuckytrio (MBT), a three‐buckyball system, as a modular platform for a family of structurally defined metallofullerene derivatives that can safely carry rare‐earth elements.